2013
DOI: 10.4081/mrm.2013.548
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic usefulness of pregnancy-associated plasma protein-A in suspected pulmonary embolism

Abstract: Background: The role of biomarkers for prognostication and diagnosis of pulmonary embolism (PE) is increasing. It has been reported that pregnancy-associated plasma protein-A (PAPP-A) can be used as a proatherosclerotic marker. The present study was aimed to evaluate whether PAPP-A levels are helpful in the differential diagnosis of patients presenting with suspected PE. Methods: 53 consecutive patients evaluated for suspected PE were prospectively enrolled in the study. Serum PAPP-A levels were measured in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…-A) belongs to the metalloproteinase family. PAPP-A is synthesized by the placenta during pregnancy; therefore, it is widely used as a marker for prenatal genetic screening [27]. Moreover, PAPP-A is produced by the colon, kidneys, endometrium, bones, and testicles, among other organs [28].…”
Section: Oxidative Stress In Osamentioning
confidence: 99%
“…-A) belongs to the metalloproteinase family. PAPP-A is synthesized by the placenta during pregnancy; therefore, it is widely used as a marker for prenatal genetic screening [27]. Moreover, PAPP-A is produced by the colon, kidneys, endometrium, bones, and testicles, among other organs [28].…”
Section: Oxidative Stress In Osamentioning
confidence: 99%
“…Fialova et al found a positive correlation between PAPP-A and CRP levels in patients who underwent dialysis [ 30 ]. In patients diagnosed with pulmonary embolism, it was reported that there were no correlations between the PAPP-A levels and inflammatory markers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…PAPP-A is first synthesized by placenta trophoblasts during pregnancy. It is used for Down Syndrome screening in pregnancy [ 16 ]. In addition to trophoblasts, PAPP-A is reported to be synthesized in endometrium, testicle, kidney, bone, colon and other adult and fetal tissues [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation